PENDAMPINGAN MASYARAKAT DALAM BUDIDAYA PORANG SECARA AGROFORESTRI SEBAGAI RINTISAN DESA ALASOMBO, SUKOHARJO SEBAGAI SENTRA PORANG - Widyatmani Sih Dewi; Vita Ratri Cahyani; Mujiyo Mujiyo; Ferina Pungky (Universitas Sebelas Maret, 2021)
Community Assistance in Porang Cultivation in Agroforestry to Realize Alasombo as a Porang Center. Land conditions in Alasombo Village, Sukoharjo Regency, Central of Java potentially to be developed as a centre for porang (Amorphophallus muelleri Blume). The purpose of community service (PKM) is to introduce and improve skills in agroforestry cultivation of porang to realize Alasombo as a porang centre. PKM partners are ASSTI Farmer Groups and Youth Groups in Bende, Alasombo. The methods used were focus group discussion (FGD), cultivation practices, and evaluation. The activity was carried out from April to December 2020. Cultivation practices were carried out in Bende. The results of PKM activities show that 52.2% of the people know that for porang tubers have a high selling price and are very potential as an export commodity, 60.9% of the people do not know how to cultivate porang properly, 56.53% do not know that porang can be produced by agroforestry, and 95.5% people do not understand that the physical, chemical and biological properties of soil affect the growth and yield of porang. Assistance by universities is essential for the transfer of knowledge and technology to the community. Continuous assistance activities need to be carried out to make Alasombo a centre for Amorphophalus sp. `